Universal banking : the effects of diversification on bank profits in a low interest world - Angelica, Halim Lim (Nanyang Technological University, 2020)
This paper aims to determine the impact of diversification of banks’ activities on their profitability, under the universal banking model. A universal bank provides a one-stop-shop for all financial services to consumers. We examined a panel dataset consisting of 47 NYSE-listed US banks from 2009 to 2017. In this post-crisis period of low-interest-rate environment, we found that a more diversified bank would generally enjoy greater returns, after controlling for certain bank-specific factors. Furthermore, we also found that for our sample, banks that maintained approximately 18% of interest revenue from their operations could maximise their profit.